2020
DOI: 10.5604/01.3001.0014.3431
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative depression in patients after coronary artery bypass grafting (CABG) – a review of the literature

Abstract: <b>Introduction:</b> Ischemic heart disease is the most common cause of death in the world. The lives of patients with vascular defects can be saved by coronary artery bypass grafting (CABG). However, it is associated with an increased risk of developing depression after surgery. <br><b>Meterial and Methods:</b> The aim of the study is to present the results of the latest research on postoperative depression after CABG, including studies describing the course of the disease, its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In the current study, an a priori risk of depression was observed in 29.03% of patients. A literature review indicated that the prevalence of depression after cardiac surgery is between 15% and 40%, and symptoms of depression can be identified in up to 60% [ 2 , 3 , 4 , 28 , 29 ]. Thus, our results are in line with those of other authors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, an a priori risk of depression was observed in 29.03% of patients. A literature review indicated that the prevalence of depression after cardiac surgery is between 15% and 40%, and symptoms of depression can be identified in up to 60% [ 2 , 3 , 4 , 28 , 29 ]. Thus, our results are in line with those of other authors.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression in this particular group of patients varies between studies and ranges from 13% to 40% of patients. In some patients, it may be a long-term problem, becoming a chronic condition [ 2 , 3 , 4 ]. The increasing number of cardiac surgeries worldwide is leading to a large group of people suffering from depression after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HCR integrates bridging between the left internal mammary artery and the anterior descending artery with PCI of other vessels and can provide effective treatment for different types of CAD. Traditional CABG gradually has been replaced in the last decade, and previous studies have found that dangerous events, such as depression [Stanicki 2020], stroke [Newman 2001;Tarakji 2011], and delirium [Martin 2012] occur after CABG, which not only decreases the quality of life but also worsens the prognosis of patients. Moreover, some patients have concomitant diseases in clinical practice, such as diabetes mellitus, chronic obstructive pulmonary disease, ascending aortic disease, peripheral vascular disease, and malignancies.…”
Section: Introductionmentioning
confidence: 99%